PENGARUH KECANDUAN INTERNET DAN MATERIALISME TERHADAP PERILAKU PEMBELIAN KOMPULSIF ONLINE - Wulandari, Kurnianingtias (E-Jurnal Manajemen; Vol 7 No 2 (2018)DO - 10.24843/EJMUNUD.2018.v7.i02.p17, 2018)
ABSTRACT This study was conducted to determine the effect of internet addiction and materialism on online compulsive buying behavior.  This study is done by targeting Indonesian internet users. The number of samples are 80  respondent by using purposive sampling method. The data was collected by distributing online questionnaires using Likert scales 5 points to measure 16 indicators. The result of this study indicate that internet addiction and materialism have a positive and significant impact on online compulsive buying behavior. Based on research results as much as someone spends their time on the internet as well as as having a materialist mindset tend to have online compulsive buying behavior. This phenomenon is an opportunity that can be utilized by marketers to design a strategy that is able to encourage potential customers to be interested and buy the offered products.